2007
DOI: 10.1007/s12010-007-8009-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cyclodextrin Glucanotransferase Produced by Bacillus megaterium

Abstract: Cyclodextrin glucanotransferase, produced by Bacillus megaterium, was characterized, and the biochemical properties of the purified enzyme were determined. The substrate specificity of the enzyme was tested with different alpha-1,4-glucans. Cyclodextrin glucanotransferase displayed maximum activity in the case of soluble starch, with a Km value of 3.4 g/L. The optimal pH and temperature values for the cyclization reaction were 7.2 and 60 degrees C, respectively. The enzyme was stable at pH 6.0-10.5 and 30 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
1
17
0
3
Order By: Relevance
“…). The amount of enzyme synthesized by the test microorganism in the present study was in the production range reported in the literature (Table ) . In the present study excessive foaming was observed in the test ALR–NDTs and by use of low gas flow rate and antifoam reagent the test system was controlled.…”
Section: Resultssupporting
confidence: 56%
“…). The amount of enzyme synthesized by the test microorganism in the present study was in the production range reported in the literature (Table ) . In the present study excessive foaming was observed in the test ALR–NDTs and by use of low gas flow rate and antifoam reagent the test system was controlled.…”
Section: Resultssupporting
confidence: 56%
“…Gawande and Patkar [12] reported that the temperature stability of the enzyme was improved in the presence of a substrate at 40 • C. It is possible that CGTase could maintain their active structure at high temperature by binding with substrate. Kim et al [20] and Pishtiyski et al [21] also found that the stability of CGTase increased with the presence of starch. This phenomenon is due to the adsorption of CGTase on the starch surface that protects the enzyme against denaturation [22].…”
Section: Effect Of Substrate Concentration and Temperature On Thermalmentioning
confidence: 93%
“…I-5β(Shim et al 2004) Anaerobranca gottschalkii α(Thiemann et al 2004) Bacillus circulans 8β(Nitschke et al 1990) Bacillus circulans 251β(Lawson et al 1994) Bacillus circulans A11β(Rimphanitchayakit et al 2005) Bacillus circulans DF 9Rα/β(Marechal et al 1996) Bacillus clarkii 7384γ(Takada et al 2003) Bacillus clausii E16 a β(Alves-Prado et al 2008) Bacillus firmus 290-3β/γ(Englbrecht et al 1988) Bacillus firmus 7B a β(Moriwaki et al 2007) Bacillus firmus NCIM 5119 a β(Gawande et al 1999) Bacillus firmus no. 37 a β(Matioli et al 2001) Bacillus licheniformis α/β(Hill et al 1990) Bacillus macerans b α(Takano et al 1986) Bacillus megaterium a β(Pishtiyski et al 2008) Bacillus obhensis β(Sin et al 1991) Bacillus sp. B1018β(Itkor et al 1990) Bacillus sp.…”
Section: Productionmentioning
confidence: 99%